Effects of pitch, yaw, and roll on delta wing skin friction topology. (March 2016) - Woodiga, Sudesh; Liu, Tianshu; Ramasamy, RS Vewen; Kode, Sai Kumar
High-resolution skin friction fields in separated flows over a 65° delta wing and a 76/40° double-delta wing with different junction fillets are obtained by using quantitative global skin friction diagnostics based on luminescent oil visualizations. The topological features such as separation and attachment lines on these delta wings are identified, and the effects of the pitch, yaw, and roll angles on the skin friction topology are studied systematically. The topological consistency of the measured skin friction fields on the delta wings is examined by using the Poincare–Bendixson index formula.